The acceptability of environmental education kit (EE) kit among teachers at selected schools in Peninsular Malaysia - Sulaiman, Siti Hajar; Tengku Ismail, Tengku Hanidza; Harun, Rosta (IDOSI Publications, 2012)
A qualitative study was conducted in an attempt to assess the use of the Environmental Education Kit (EE) Kit among teachers in Peninsular Malaysia. The study was conducted on teachers from four selected secondary schools, representing four school zones in Malaysia in April and May 2011. As a pilot study, only these schools receive the EE Kit. Data was collected through face-to-face interviews. Among 85 teachers, 15 volunteered to be interviewed. This study aimed to describe and analyze the experience of using the EE Kit for teaching environmental education components in the classroom. Four elements were discussed to represent the acceptability towards the EE Kit. This study revealed 73% (11/15) of the interviewee have positive views towards using the EE Kit. Four factors were identified as barriers to adopting the EE Kit: (i) Limited time, (ii) Limited audio-visual equipment, (iii) Limited access to the EE Kit and (iv) Language problem.